Balloon valvuloplasty for congenital aortic stenosis: Multi‐center safety and efficacy outcome assessment. Issue 5 (29th May 2015) - Torres, Alejandro; Vincent, Julie A.; Everett, Allen; Lim, Scott; Foerster, Susan R.; Marshall, Audrey C.; Beekman, Robert H.; Murphy, Joshua; Trucco, Sara M.; Gauvreau, Kimberlee; Holzer, Ralf; Bergersen, Lisa; et al.
<x xml:space="preserve">Abstract</x> Objective To describe contemporary outcomes of balloon aortic valvuloplasty (BAVP) performed in 22 US centers. Background: BAVP constitutes first‐line therapy for congenital aortic stenosis (cAS) in many centers. Methods We used prospectively‐collected data from two active, multi‐institutional, pediatric cardiac catheterization registries. Acute procedural success was defined, for purposes of this review, as a residual peak systolic gradient ≤ 35 mm Hg and no more than mild aortic regurgitation (AR) for patients with isolated cAS. For patients with mixed aortic valve disease, a residual peak systolic gradient ≤ 35 mm Hg without worsening of AR was considered successful outcome. Results In 373 patients with a median age of 8 months (1 day to 40 years of age) peak systolic gradient had a median of 59 [50, 71] mm Hg pre‐BAVP and 22 [15, 30] mm Hg post‐BAVP (P < 0.001). Procedural success was achieved in 160 patients (71%). The factors independently associated with procedural success were: first time intervention (OR = 2.0 (1.0, 4.0) P = 0.04), not‐prostaglandin dependent, (OR=3.5 (1.5, 8.1); P = 0.003), and isolated cAS (absence of AR) (OR = 2.1 (1.1–3.9); P = 0.03). Twenty percent of patients experienced adverse events, half of which were of high severity. There was no procedural mortality. Neonatal status was the only factor associated with increased risk of high severity adverse events (OR 3.7; 95% CI 1.5–9.0). Conclusion In the current era, BAVP results in procedural success (gradient reduction with minimal increase in AR) in 71% of patients treated at US centers where BAVP is considered first‐line therapy relative to surgery. © 2015 Wiley Periodicals, Inc.